News from the Field: Gold Hoard Found at Capernaum - Weiss, Herold (The Biblical archaeology review, 1983)
I had not come in search of gold. I was an academician, seeking only to understand. Until 1980, I had been an armchair archaeologist. Then I accepted an invitation to become associate director of the volunteer program of a dig at Capernaum. That summer, I worked in a residential quarter of the city about […]